Scientific American. – 1865. – Vol. 13, № 2 - б/а (New York. Munn @ Company, 1865)
A weekly journal of practical information in art, science, mechanics, chemistry and manufactures.
Scientific American. Vol. 13, N 1–16. – New York, 1865. – P. 1–254.
Keywords: July 8, 1865; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of technology and industry; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of science and ideas; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::Agricultural history; Research Subject Categories::NATURAL SCIENCES::Physics; Research Subject Categories::NATURAL SCIENCES::Chemistry; Research Subject Categories::SOCIAL SCIENCES::Other social sciences::Mass communication; Recent American Patents; Patents; Flautt’s Self-Setting Trap; Broughton’s Gage Cock; Van Anden’s American Mower; Chapman’s Self-Feeding Ratchet Wrench; Tarbox’s Double-Faced Sad Iron